Graphene-nickel oxide composite material prepared based on one-step hydrothermal method and application of graphene-nickel oxide composite material in preparation of lithium ion battery

The preparation of graphene-nickel oxide composite materials by one-step hydrothermal method solves the problem of insufficient conductivity and structural stability of nickel oxide in lithium-ion batteries, and achieves high specific capacitance, good rate capability and good long-term cycle stability.

CN119650615APending Publication Date: 2025-03-18ELECTRIC POWER RES INST OF GUANGXI POWER GRID CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411609351.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The theoretical capacity of commercial graphite used in existing lithium-ion batteries is limited, and the high resistance and structural stability of transition metal oxides such as nickel oxides lead to poor rate capability and cycle stability.

Method used

A graphene-nickel oxide composite material is prepared by a one-step hydrothermal method. By heating graphene powder and nickel oxide in a mixed solution of a specific ratio, a composite material with a peony-like 3D structure is formed, which improves its surface area, electrical conductivity and mechanical flexibility.

Benefits of technology

The conductivity and cyclic stability of graphene-nickel oxide composite materials are improved, the binding energy between nickel oxide and graphene is enhanced, and the capacity and long-term cyclic stability of lithium-ion batteries are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650615A_ABST
    Figure CN119650615A_ABST
Patent Text Reader

Abstract

The invention discloses a graphene-nickel oxide composite material prepared on the basis of a one-step hydrothermal method and application of the graphene-nickel oxide composite material in preparation of a lithium ion battery, NiO is integrated into a graphene nanostructure, so that a unique thin nanosheet array with a porous conductive channel is generated, and meanwhile, in the composite material, the graphene-nickel oxide composite material has good electrochemical performance. NiO generates controllable aggregation and re-accumulation, which can buffer electrode stress and improve conductivity, graphene is also beneficial to insertion of lithium ions compared with common graphite, and the added graphene not only improves the conductivity, but also can be used as a flexible substrate of NiO to prevent NiO particles from diffusing into electrolyte in the circulation process. In addition, due to the unique layered hollow structure of NiO, the electrode stress can be reduced by controlling the volume change, and the electrochemical reaction kinetics is greatly improved. The cycling stability and the capacity of the lithium ion battery are effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of battery energy storage technology utilization, and specifically relates to a graphene-nickel oxide composite material prepared based on a one-step hydrothermal method and its application in the preparation of lithium-ion batteries. Background Art

[0002] At present, the consumption of fossil fuels and the increase of environmental pollution are becoming more and more stringent, and more efficient, cleaner and renewable energy sources are urgently needed. Common sustainable energy sources (wind energy, solar energy, tidal energy and geothermal energy) have seasonal characteristics, so they require special equipment for energy conversion and storage to improve the efficiency and sustainability of energy systems. In many application fields, the most effective and practical energy conversion and storage devices are batteries, supercapacitors, solar cells, fuel cells, nuclear batteries, etc. Among them, lithium-ion batteries as a new type of energy storage device have a strong appeal to researchers. Lithium-ion batteries are considered to be one of the most promising power sources for mobile, portable electronics and electric vehicles because of their excellent energy efficiency, high battery potential, low cost and long cycle life. However, the commercial graphite used in lithium-ion batteries is limited to 372mAh / g due to its limited theoretical capacity, which is not enough to meet the current market demand.

[0003] As potential high-energy alternatives, transition metal oxides (TMOs), such as Co, Ni, Fe, Cu, Ti and Zn oxides and their composites, have attracted research attention due to their excellent storage capacity and high energy density of about 700 mAh / g. However, the high resistance of transition metal oxides leads to poor rate capability. At the same time, due to poor structural stability, loss of active materials or peroxidation decomposition, they usually show low cycle stability during long-term charge-discharge. Therefore, in order to compensate for the shortcomings of transition metal oxides, there are currently two effective methods: first, reducing the particle size to nanometers to increase the effective surface area and shorten the diffusion path of ions / electrons; second, combining conductive carbon materials with transition metal oxides with excellent electrochemical properties. In this regard, the most common strategy is to support the metal oxide on the carbon material or wrap it with a carbon layer to provide enhanced rate capability and cycle performance.

[0004] Among metal oxides, nickel oxide (NiO) is a very promising anode for lithium-ion batteries due to its abundance, low cost, eco-friendliness, enviable safety, and high volumetric energy density. However, like other oxides, pristine NiO utilization is obviously not an effective anode for lithium-ion batteries due to its poor conductivity, low rate capability, and limited cyclability. Combining NiO with carbon nanostructures such as graphite, hard carbon, carbon nanofibers, and carbon nanotubes can not only provide a larger surface area, but also provide higher conductivity and desirable mechanical flexibility, thereby buffering the volume expansion of NiO.

[0005] Graphite-nickel oxide (NiO) composites have been studied for use as anodes in lithium-ion batteries. However, developing an ideal composite material that overcomes the conductivity limitations of NiO remains a challenge. Therefore, in order to achieve high-performance lithium-ion batteries with nickel oxide materials as anodes, it is very necessary to improve the ionic conductivity of the NiO anode. Summary of the invention

[0006] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0007] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0008] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a graphene-nickel oxide composite material based on a one-step hydrothermal method.

[0009] In order to solve the above technical problems, the present invention provides the following technical solution: a method for preparing a graphene-nickel oxide composite material based on a one-step hydrothermal method, comprising:

[0010] Mixing nickel sulfate hexahydrate, sodium acetate trihydrate, sodium citrate and deionized water to prepare a mixed solution;

[0011] The graphene powder is dissolved in the mixed solution, and after being uniformly mixed by ultrasonication, it is heated at 180-200°C for 20-22h in a sealed autoclave. After the autoclave is naturally cooled to room temperature, the obtained graphene-nickel oxide composite is centrifuged, washed with ethanol and water, and freeze-dried to obtain a graphene-nickel oxide composite material.

[0012] As a preferred embodiment of the method of the present invention, the ratio of nickel sulfate hexahydrate, sodium acetate trihydrate, sodium citrate and deionized water is 0.02 mol: 0.1 mol: 0.05 mol: 100 ml.

[0013] As a preferred embodiment of the method of the present invention, the ratio of the graphene powder to nickel sulfate hexahydrate is 250 mg:0.02 mol.

[0014] As a preferred embodiment of the method of the present invention, the reaction temperature in the autoclave is 200° C. and the heating reaction time is 20 h.

[0015] Another object of the present invention is to overcome the deficiencies in the prior art and provide a graphene-nickel oxide composite material.

[0016] Another object of the present invention is to overcome the deficiencies in the prior art and provide an application of a graphene-nickel oxide composite material in the preparation of a lithium ion battery, comprising: placing a negative electrode shell, a spring sheet, a current collector, a negative electrode material, a separator, a positive electrode material, and a positive electrode shell in an anaerobic glove box from bottom to top;

[0017] Taking out the lithium-ion battery from the glove box, placing it on a lithium-ion battery pressing table, pressurizing it to 5 bar, and removing the lithium-ion battery from the table to obtain the lithium-ion battery;

[0018] The preparation method of the negative electrode material is as follows: 85wt% of the graphene-nickel oxide composite material and 10wt% of acetylene carbon are mixed in a watch glass until a uniform black powder is obtained, and then 5w% of polytetrafluoroethylene PTFE and ethanol are added to form a slurry;

[0019] The slurry was coated on nickel foam, dried in air at 60°C for 12 h, and pressed into a film at 10 MPa to obtain the negative electrode material.

[0020] As a preferred embodiment of the application of the present invention, the slurry is coated on nickel foam, wherein 1 cm 2 The nickel foam contains 2 mg of graphene-nickel oxide composite material.

[0021] Beneficial effects of the present invention:

[0022] (1) The present invention provides a simple hydrothermal method to synthesize a graphene-nickel oxide composite material for the negative electrode of a lithium ion battery. The obtained composite material has a peony-shaped 3D structure, which can provide a larger surface area, higher conductivity and ideal mechanical flexibility, thereby coping with the change in the volume of nickel oxide during the charge and discharge process and preventing the agglomeration of graphene sheets; at the same time, the appropriate graphene content can improve the conductivity and enhance the binding energy between nickel oxide and graphene, thereby improving the battery capacity and cycle stability; therefore, the optimal graphene-nickel oxide composite material has excellent performance, including high specific capacitance, good rate capability, and good long-term cycle stability; therefore, the present invention solves the problem of low ionic conductivity of nickel oxide, making graphene-nickel oxide materials promising for use in high-performance metal oxide lithium ion batteries.

[0023] (2) The present invention provides a lithium-ion battery based on a graphene-nickel oxide composite electrode prepared by a one-step hydrothermal method, in which NiO is integrated into a graphene nanostructure, thereby producing a unique thin nanosheet array with porous conductive channels. At the same time, in this composite material, NiO produces controllable aggregation and re-stacking, which can buffer electrode stress and improve conductivity. Compared with ordinary graphite, graphene is also more conducive to the insertion of lithium ions. Among them, the addition of graphene not only improves the conductivity, but also serves as a flexible substrate for NiO to prevent NiO particles from diffusing into the electrolyte during the cycle. In addition, the unique layered hollow structure of NiO can also reduce electrode stress by controlling volume changes, which is conducive to promoting the rapid migration of electrolyte ions to electroactive sites and achieving close contact between electrode materials and electrolytes, greatly improving the kinetics of electrochemical reactions.

[0024] (3) The present invention effectively improves the cycle stability and capacity of lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0026] Figure 1 Schematic diagram of the structure of a lithium-ion battery with a graphene-nickel oxide composite electrode in an embodiment of the present invention. DETAILED DESCRIPTION

[0027] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0028] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0029] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0030] Example 1

[0031] The present invention provides a lithium ion battery based on a graphene-nickel oxide electrode prepared by a one-step hydrothermal method, Figure 1 It is explained that the lithium-ion battery structure is stacked from bottom to top in sequence: negative electrode shell 100, spring sheet 200, current collector 300, negative electrode material 400, separator 500, positive electrode material 600, positive electrode shell 700;

[0032] The main preparation steps are as follows:

[0033] Step 1: Dissolve 0.02 mol of nickel sulfate hexahydrate (NiSO4·6H2O), 0.1 mol of sodium acetate trihydrate (C2H9NaO5), and 0.05 mol of sodium citrate (C6H5Na3O7) in 100 ml of deionized water.

[0034] Step 2: Weigh the drug, disperse 250 mg of graphene powder into the solution obtained in step 1, and ultrasonicate for 1 h.

[0035] Step 3: Prepare the nickel oxide-graphene composite by a one-step hydrothermal method, transfer the mixed solution into a Teflon-lined stainless steel autoclave, seal the autoclave, and heat it at 200°C for 20h.

[0036] Step 4: After the reactor is naturally cooled to room temperature, the obtained graphene-nickel oxide composite is centrifuged, washed with ethanol and water, and then freeze-dried.

[0037] Step 5: 85wt% of the graphene-nickel oxide composite material and 10wt% of acetylene carbon were mixed in a watch glass until a uniform black powder was obtained, and then 5w% of polytetrafluoroethylene PTFE and ethanol were added to form a slurry. The obtained product was slurried and coated on a nickel foam substrate (1cm 2 The nickel foam contained 2 mg of graphene-nickel oxide composite material and was placed in a vacuum oven and dried at 120°C for 3 h.

[0038] Step 6: Sinter the obtained product at 350°C for 12 h in an Ar atmosphere with a heating rate of 2°C / min.

[0039] Step 7: Electrode preparation: take the obtained product out of the furnace and cut the product into electrode discs using an electrode cutting machine.

[0040] Step 8: Lithium-ion battery assembly: enter the oxygen-free glove box, and place the negative electrode shell 100, spring sheet 200, current collector 300, negative electrode material 400, separator 500, positive electrode material 600, and positive electrode shell 700 in order from bottom to top;

[0041] Take out the lithium-ion battery from the glove box, put it into the lithium-ion battery pressing table, pressurize it to about 5 bar, and remove the lithium-ion battery from the table.

[0042] Comparative Example 1

[0043] Step 1: Dissolve 0.02 mol of nickel sulfate hexahydrate (NiSO4·6H2O) and 0.15 mol of sodium citrate (C6H5Na3O7) in 100 ml of deionized water.

[0044] Step 2: Weigh the drug, disperse 250 mg of graphene powder into the solution obtained in step 1, and ultrasonicate for 1 h.

[0045] Step 3: Prepare the nickel oxide-graphene composite by a one-step hydrothermal method, transfer the mixed solution into a Teflon-lined stainless steel autoclave, seal the autoclave, and heat it at 200°C for 20h.

[0046] Step 4: After the reactor is naturally cooled to room temperature, the obtained graphene-nickel oxide composite is centrifuged, washed with ethanol and water, and then freeze-dried.

[0047] Step 5: 85wt% of the graphene-nickel oxide composite material and 10wt% of acetylene carbon were mixed in a watch glass until a uniform black powder was obtained, and then 5w% of polytetrafluoroethylene PTFE and ethanol were added to form a slurry. The obtained product was slurried and coated on a nickel foam substrate (1cm 2 The nickel foam contained 2 mg of graphene-nickel oxide composite material and was placed in a vacuum oven and dried at 120°C for 3 h.

[0048] Step 6: Sinter the obtained product at 350°C for 12 h in an Ar atmosphere with a heating rate of 2°C / min.

[0049] Step 7: Electrode preparation: take the obtained product out of the furnace and cut the product into electrode discs using an electrode cutting machine.

[0050] Comparative Example 2

[0051] Step 1: Dissolve 0.02 mol of nickel sulfate hexahydrate (NiSO4·6H2O) and 0.15 mol of sodium acetate trihydrate (C2H9NaO5) in 100 ml of deionized water.

[0052] Step 2: Weigh the drug, disperse 250 mg of graphene powder into the solution obtained in step 1, and ultrasonicate for 1 h.

[0053] Step 3: Prepare the nickel oxide-graphene composite by a one-step hydrothermal method, transfer the mixed solution into a Teflon-lined stainless steel autoclave, seal the autoclave, and heat it at 200°C for 20h.

[0054] Step 4: After the reactor is naturally cooled to room temperature, the obtained graphene-nickel oxide composite is centrifuged, washed with ethanol and water, and then freeze-dried.

[0055] Step 5: 85wt% of the graphene-nickel oxide composite material and 10wt% of acetylene carbon were mixed in a watch glass until a uniform black powder was obtained, and then 5w% of polytetrafluoroethylene PTFE and ethanol were added to form a slurry. The obtained product was slurried and coated on a nickel foam substrate (1cm 2 The nickel foam contained 2 mg of graphene-nickel oxide composite material and was placed in a vacuum oven and dried at 120°C for 3 h.

[0056] Step 6: Sinter the obtained product at 350°C for 12 h in an Ar atmosphere with a heating rate of 2°C / min.

[0057] Step 7: Electrode preparation: take the obtained product out of the furnace and cut the product into electrode discs using an electrode cutting machine.

[0058] Comparative Example 3

[0059] Step 1: Dissolve 0.02 mol of nickel sulfate hexahydrate (NiSO4·6H2O) and 0.15 mol of hexamethylenetetramine in 100 ml of deionized water.

[0060] Step 2: Weigh the drug, disperse 250 mg of graphene powder into the solution obtained in step 1, and ultrasonicate for 1 h.

[0061] Step 3: Prepare the nickel oxide-graphene composite by a one-step hydrothermal method, transfer the mixed solution into a Teflon-lined stainless steel autoclave, seal the autoclave, and heat it at 200°C for 20h.

[0062] Step 4: After the reactor is naturally cooled to room temperature, the obtained graphene-nickel oxide composite is centrifuged, washed with ethanol and water, and then freeze-dried.

[0063] Step 5: 85wt% of the graphene-nickel oxide composite material and 10wt% of acetylene carbon were mixed in a watch glass until a uniform black powder was obtained, and then 5w% of polytetrafluoroethylene PTFE and ethanol were added to form a slurry. The obtained product was slurried and coated on a nickel foam substrate (1cm 2 The nickel foam contained 2 mg of graphene-nickel oxide composite material and was placed in a vacuum oven and dried at 120°C for 3 h.

[0064] Step 6: Sinter the obtained product at 350°C for 12 h in an Ar atmosphere with a heating rate of 2°C / min.

[0065] Step 7: Electrode preparation: take the obtained product out of the furnace and cut the product into electrode discs using an electrode cutting machine.

[0066] The lithium sheet was used as the counter electrode and the electrolyte was commercially available 1mol / L LiPF6 / EC + The DMC solution was tested for charge and discharge performance using a battery tester. The resulting product was used as a negative electrode material for a lithium-ion battery and was tested for cycle stability at a current density of 100 mA / g. The battery capacity retention rate after 100 cycles is shown in Table 1 below.

[0067] Battery capacity retention rate (%) = (battery capacity after 100 cycles / initial battery capacity) × 100%

[0068] Table 1

[0069]

[0070] It can be seen that the graphene-nickel oxide composite material prepared in the present invention has good long-term cycle stability.

[0071] The present invention provides a simple hydrothermal method for synthesizing a graphene-nickel oxide composite material for a negative electrode of a lithium ion battery. The obtained composite material has a peony-shaped 3D structure, which can provide a larger surface area, higher conductivity and ideal mechanical flexibility, thereby coping with the change in the volume of nickel oxide during the charge and discharge process and preventing the agglomeration of graphene sheets; at the same time, a suitable graphene content can improve the conductivity and enhance the binding energy between nickel oxide and graphene, thereby improving the battery capacity and cycle stability; therefore, the optimal graphene-nickel oxide composite material has excellent performance, including high specific capacitance, good rate capability, and good long-term cycle stability; therefore, the present invention solves the problem of too low ionic conductivity of nickel oxide, making it possible for graphene-nickel oxide materials to be used in high-performance metal oxide lithium ion batteries.

[0072] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.

Claims

1. A method for preparing a graphene-nickel oxide composite material based on a one-step hydrothermal method, characterized in that: include, Mixing nickel sulfate hexahydrate, sodium acetate trihydrate, sodium citrate and deionized water to prepare a mixed solution; The graphene powder is dissolved in the mixed solution, and after being uniformly mixed by ultrasonication, it is heated at 180-200°C for 20-22h in a sealed autoclave. After the autoclave is naturally cooled to room temperature, the obtained graphene-nickel oxide composite is centrifuged, washed with ethanol and water, and freeze-dried to obtain a graphene-nickel oxide composite material.

2. The method according to claim 1, characterized in that: The ratio of nickel sulfate hexahydrate, sodium acetate trihydrate, sodium citrate and deionized water is 0.02 mol: 0.1 mol: 0.05 mol: 100 ml.

3. The method according to claim 1 or 2, characterized in that: The ratio of the graphene powder to nickel sulfate hexahydrate is 250 mg:0.02 mol.

4. The method according to claim 3, characterized in that: The reaction temperature in the autoclave is 200° C., and the heating reaction time is 20 h.

5. A graphene-nickel oxide composite material obtained by the method according to any one of claims 1 to 4.

6. Use of the graphene-nickel oxide composite material according to claim 5 in the preparation of lithium ion batteries.

7. The use according to claim 6, characterized in that: include, In an anaerobic glove box, a negative electrode shell (100), a spring sheet (200), a current collector (300), a negative electrode material (400), a separator (500), a positive electrode material (600), and a positive electrode shell (700) are placed in order from bottom to top; Taking out the lithium-ion battery from the glove box, placing it on a lithium-ion battery pressing table, pressurizing it to 5 bar, and removing the lithium-ion battery from the table to obtain the lithium-ion battery; The preparation method of the negative electrode material is as follows: 85wt% of the graphene-nickel oxide composite material and 10wt% of acetylene carbon are mixed in a watch glass until a uniform black powder is obtained, and then 5w% of polytetrafluoroethylene PTFE and ethanol are added to form a slurry; The slurry was coated on nickel foam, dried in air at 60°C for 12 h, and pressed into a film at 10 MPa to obtain the negative electrode material.

8. The use according to claim 7, characterized in that: The slurry is coated on nickel foam, wherein 1 cm 2 The nickel foam contains 2 mg of graphene-nickel oxide composite material.